Case report: Significant response of alpha-fetoprotein-producing gastric cancer from combined chemotherapy and immunotherapy - Da, Xue; Juan, Zhang; Zhijun, Hu; Zhongchuan, Lyu (Frontiers in Immunology, 2024)
Alpha-fetoprotein-producing gastric cancer (AFPGC) represents a particularly aggressive subtype of gastric carcinoma characterised by elevated rates of vascular invasion ［ 1 ］ , lymphatic dissemination, hepatic metastasis, and an unfavourable clinical outcome ［ 2 ］ .Treatment strategies for AFPGC have historically lacked specificity. Herein, a case is presented involving AFPGC in which the patient exhibited a notable response to combined anti-PD-1 antibody immunotherapy and SOX chemotherapy, potentially achieving a cure.